Evaluation of PAX3 genetic variants and nevus number. (4th July 2013) - Ogbah, Zighereda; Badenas, Celia; Harland, Mark; Puig‐Butille, Joan A.; Elliot, Fay; Bonifaci, Nuria; Guino, Elisabet; Randerson‐Moor, Julie; Chan, May; Iles, Mark M.; Glass, Daniel; Brown, Andrew A.; et al.
Summary: The presence of a high nevus number is the strongest phenotypic predictor of melanoma risk. Here, we describe the results of a three‐stage study directed at identifying risk variants for the high nevus phenotype. At the first stage, 263 melanoma cases from Barcelona were genotyped for 223 single‐nucleotide polymorphisms (SNPs) in 39 candidate genes. Seven SNPs in the PAX3 gene were found to be significantly associated with nevus number under the additive model. Next, the associations for seven PAX3 variants were evaluated in 1217 melanoma cases and 475 controls from Leeds; and in 3054 healthy twins from TwinsUK. Associations with high nevus number were detected for rs6754024 (P values < 0.01) in the Barcelona and Leeds datasets and for rs2855268 (P values < 0.01) in the Barcelona and the TwinsUK sets. Associations (P values < 0.001) in the opposite direction were detected for rs7600206 and rs12995399 in the Barcelona and TwinsUK sets. This study suggests that SNPs in PAX3 are associated with nevus number, providing support for PAX3 as a candidate nevus gene. Further studies are needed to examine the role of PAX3 in melanoma susceptibility.